2020
DOI: 10.1108/ejim-10-2019-0306
|View full text |Cite
|
Sign up to set email alerts
|

Innovations and firm-level efficiency: a comparative analysis between China and India

Abstract: PurposeThis study examines the innovation-efficiency linkage for Indian and Chinese manufacturing and service firms.Design/methodology/approachWe applied the stochastic production and cost frontier approach to determine the output and cost efficiency of the firms surveyed in World Bank enterprise surveys. We then used both unconditional and conditional propensity score matching (PSM) estimation techniques to examine the effects of innovation as well as R&D on output and cost efficiency of the firms surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…The linkage between IT investments and sectoral efficiency has been a widely studied area in the literature (Berger and Mester, 1997; Beccalli, 2007; Kwateng et al , 2019; Tian et al , 2019; Phan et al , 2020; Islam and Fatema, 2020). However, relatively few studies acknowledge the nonmonotonic influence of IT on efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The linkage between IT investments and sectoral efficiency has been a widely studied area in the literature (Berger and Mester, 1997; Beccalli, 2007; Kwateng et al , 2019; Tian et al , 2019; Phan et al , 2020; Islam and Fatema, 2020). However, relatively few studies acknowledge the nonmonotonic influence of IT on efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, R&D expenditure plays a vital role in improving efficiency (Asongu et al , 2017, Hu et al , 2019; Tian et al , 2019; Phan et al , 2020; Islam and Fatema, 2020; Juhro et al , 2020). Hollanders and Esser (2007) contend that R&D is related to the concept of productivity.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Ferreira et al (2020) used many things related to R&D (Research and Development) in measuring the innovation variables conducted by SMEs in Portugal. Another study stated that R&D is the main resource for how company innovation can be conducted (Islam & Fatema, 2020).…”
Section: Relationship Of Research and Development With Innovation Str...mentioning
confidence: 99%
“…However, the literature focussing on innovation through external collaboration reports both positive and negative implications for innovation. In a comparative study between China and India, Islam and Fatema (2020) identified knowledge spillover in the Indian manufacturing sector, whereas innovation in Chinese firms is highly significant if undertaken alongside R&D. The literature suggests that there are several reasons for the positive effect of developing innovation through external collaboration, such as low resources and capabilities to respond to innovation demands (Yli-Renko et al, 2001), the capacity to deliver innovations to market (Lipparini and Sobrero, 1994), the likelihood of successful innovation (Zahra and Bogner, 2000), and finally the leverage of unique knowledge with partners (Jarillo, 1989). Conversely, studies that challenge the benefits of external collaboration in innovation argue that collaboration results in complexities in the coordination and protection of intellectual property (Kelley et al, 2009;Soh, 2003).…”
Section: Mediators Of the Innovation-performance Relationshipmentioning
confidence: 99%